Implementation of Spaced Repetition Using the SuperMemo 2 Algorithm in Memorizing Qur’anic Verses - Mhd. Mahmudi Zukri Lubis; Yusuf Ramadhan Nasution; Aidil Halim Lubis (Jurnal Ilmiah Multidisiplin Indonesia (JIM-ID), 2026)
By memorizing the verses of the Al-Qur'an a Muslim can get many virtues. However, there is one of the problems experienced by memorizing the Al-Qur'an, namely forgetting. The forgetting curve can show how quickly people forget information if they do nothing to retain the memory of the information. SuperMemo 2 is an algorithm that applies the concept of repetition and gives a certain time interval in remembering information. With the aim that the information is entered into long term memory. In the process of collecting data in this research, literature study is carried out, namely data collection techniques carried out by seeking information and knowledge sourced from books, scientific journals and other literature related to research. Based on the results of the discussion and trials that have been carried out, it is concluded that the implementation of spaced repetition using the SuperMemo 2 algorithm can run well. With the help of the Dart programming language and the Flutter SDK framework, SuperMemo 2 can be implemented and built into an application on the Android operating system. The Dart programming language is used to implement the SuperMemo 2 algorithm in the program so that it can generate interval values. Determining the interval value by the SuperMemo 2 algorithm can run well because of the influence of the ease factor which makes the interval dynamic. This allows the interval to change and adjust its value to the user's memorization ability. The interval value generated from the SuperMemo 2 algorithm will assist application users in scheduling an effective time for memorizing verses of the Qur'an.